The Empirical Change of Playing Habits among Children - Gutierrez, Ariel; Guzman, Neriza G.; Ramos, Ramilet; Uylengco, Jan Katherine A. (Future Science / FSH-PH Publications, 2022)
To maximize the growth and manage psychological distress as well as the formation of good character, children need to develop a variety of skills such as cognitive, language, self-regulation, and social-emotional skills which often appended in different outdoor traditional games. Thus, the degree of playing traditional games by the children nowadays compared with the previous generation is discussed in this study. 38 parents regardless of their status and gender were surveyed on their active participation in the traditional games as children, as well as their children’s play involvement today who are 1-12 years old. Data were collected through the created Google form link and sent via Messenger and email blasts to parents. Findings reveal that (1) significant number of children nowadays tend to play video games instead of playing traditional games; (2) safety is the utmost concern of the parents which hinder children to play some of the traditional outdoor games; and (3) the availability of mobile phones with uploaded game apps has contributed to the ignorance of traditional game playing culture.